Contemporary Digital Forensic Investigations of Cloud and Mobile Applications 2017
DOI: 10.1016/b978-0-12-805303-4.00012-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Storage as a Service Cloud Platform

Abstract: Due to the flexibility, affordability and portability of cloud storage, individuals and companies envisage the cloud storage as one of the preferred storage media nowadays. This attracts the eyes of cyber criminals, since much valuable information such as user credentials, and private customer records are stored in the cloud. There are many ways for criminals to compromise cloud services; ranging from non-technical attack methods, such as social engineering, to deploying advanced malwares. Therefore, it is vit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…It provides client-side encryption meaning that, as data leaves the client’s system, it is encrypted. Dargahi, Dehghantanha and Conti [ 55 ] conducted a forensic study of pCloud to determine what data can be found on Windows, Ubuntu, Android, and iOS operating systems when using pCloud; what data is leaked when using Google Chrme and Internet Explorer browsers on Windows operating systems; what data of forensic interest can be discovered in live memory’ and, what data can be captured in network traffic?…”
Section: Technical Advancesmentioning
confidence: 99%
See 3 more Smart Citations
“…It provides client-side encryption meaning that, as data leaves the client’s system, it is encrypted. Dargahi, Dehghantanha and Conti [ 55 ] conducted a forensic study of pCloud to determine what data can be found on Windows, Ubuntu, Android, and iOS operating systems when using pCloud; what data is leaked when using Google Chrme and Internet Explorer browsers on Windows operating systems; what data of forensic interest can be discovered in live memory’ and, what data can be captured in network traffic?…”
Section: Technical Advancesmentioning
confidence: 99%
“…In the Windows based browser experiments, uploaded file names and user names could be revealed; passwords, email addresses, file names and directories were discoverable in physical memory as Internet Explorer saves pCloud credentials in the registry. Similarly, username and passwords could be found when Google Chrome was used as the browser [ 55 ].…”
Section: Technical Advancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 illustrates a summary of mostly used tools to conduct cloud forensics [14] [24] General Drive image acquisition and offline examination Variety of investigation frameworks have been suggested for cloud forensics [25], [26]. Moreover, researchers tried to identify residual evidences of users' interactions with different cloud platforms such as DropBox [27], MEGA [28], GoogleDrive [29], SugarSync [30], pCloud [31], [32], CloudMe [33], SpiderOak [32] and hubiC [34] on Windows, Linux and mobile devices. There were several attempts to extract server-side evidences of different cloud platforms such as Syncany [35], BitTorrent Sync [36], SymForm [37] as well.…”
Section: Introductionmentioning
confidence: 99%